Genetically Modified Organism (GMO) and Its Detection Method - Sahukhal, Gyan Sundar; Jayana, Bina Laxmi; Dhungana, Nirmal; Dahal, Nawa Raj; Dawadi, Ganesh; Shrestha, Shova; Agrawal, Vishwanath Prasad (Journal of Food Science and Technology Nepal, 2009)
Genetically modified (GM) crops currently account for 29% of crop production worldwide. Despite a lack of regulations to provide for food labelling that allows for consumer preference, many products carry negative or positive labels with regard to genetic modification. Regulatory demands of labelling and traceability of GMOs in the food chain need suitable sampling protocols and analytical methods. At present, two main techniques, the DNA-based polymerase chain reaction (PCR) and the protein-based enzyme-linked immunosorbent assay (ELISA) are most widely used, although new technologies, such as microarrays, have been also developed. The main objective of this review paper is to assess the detection methods both protein based and PCR based as described by different researchers, which represents the state-of-the-art technique for GMO detection in food. Key words: GMO; Beneficial Aspects; Harmful Aspects; Detection Strategy Journal of Food Science & Technology Nepal Vol 4, September, 2008, Page: 18-22